Characterization of 30 microsatellite markers in distylous Primula sinolisteri (Primulaceae) using HiSeq sequencing. (3rd January 2019) - Wang, Xinjia; Zhong, Li; Wu, Zhikun; Sun, Huaying; Wang, Hong; Li, Dezhu; Barrett, Spencer C. H.; Zhou, Wei
Abstract : Premise of the Study: Microsatellite markers were developed for Primula sinolisteri, a perennial distylous herb belonging to section Obconicolisteri (Primulaceae), to facilitate future investigations of the population genetics and mating patterns of populations in this species. Methods and Results: We developed 30 microsatellite markers for P. sinolisteri using HiSeq X‐Ten sequencing and measured polymorphism and genetic diversity in a sample of 36 individuals from three natural populations. The markers displayed relatively high polymorphism, with the number of observed alleles per locus ranging from one to 19 (mean = 4.42). The observed and expected heterozygosity ranged from 0–1.000 and 0.083–0.882, respectively. Twenty‐nine of the loci were also successfully amplified in homostylous P. sinolisteri var. aspera . Conclusions: The microsatellite markers we have identified in P. sinolisteri provide powerful tools for investigating patterns of population genetic diversity and the evolutionary relationships between heterostyly and homostyly in this species.